Cyclical jihadist governance: the Islamic State governance cycle in Iraq and Syria. (17th November 2022) - Bamber-Zryd, Matthew
ABSTRACT: The rise and decline of the Islamic State's (IS) caliphate between 2014 and 2018 have garnered significant policy and academic attention. Explanations for the group's territorial demise have focussed on its internal group dynamics and external conflict processes. Although both explanations are valid, I adopt a historical approach to show that IS's caliphate was just one cycle in a two-decade history of governance activity. IS has undertaken three governance cycles composed of phases of insurgency, gaining territory, establishing institutions, and losing territory. After each governance cycle, IS engaged in a process of critical self-reflection and adapted its governance strategy significantly. This resulted in a progressive history in which, with each cycle, IS governed greater amounts of territory, through more complex institutions, for a longer period of time. This article is based on fieldwork interviews conducted with both IS members and civilians who lived under IS control in Iraq, Lebanon, Syria, and Turkey, as well as archival research on IS historical and contemporary governing documents.